A metal-free fluorescent probe for selective detection of histidine. (27th August 2021) - Tian, Jun; Lu, Kai; Wang, Yalin; Chen, Yu; Huo, Binyi; Jiang, Yixuan; Yu, Shanshan; Yu, Xiaoqi; Pu, Lin
Abstract: A highly selective fluorescent probe has been discovered for the recognition of L-histidine (His) without the need to use a metal cation. Mechanistic studies including 1D and 2D 1 H and 13 C NMR analyses and DFT calculation have revealed that the 2-formyl group of the 1, 1′-binaphthyl-based probe reacts with His to form a multicyclic product and the structural rigidity of this product should have contributed to the greatly enhanced fluorescence. The reactions of all the other amino acids with the probe cannot generate such a structurally rigid product and thus exhibit no or much smaller fluorescence enhancement. This probe can also be easily modified to allow the selective detection of His to be conducted in aqueous or fluorous solution. Graphical abstract: Image 1